2011
DOI: 10.2310/jim.0b013e318231db64
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Soluble Advanced Glycation End Product-Receptors and Other Soluble Serum Markers as Indicators of Diabetic Neuropathy in the Foot

Abstract: Soluble forms of the receptor for advanced glycation end product could be an endogenous protection factor against occurrence of DF, hence may be of therapeutic value in the treatment of DF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
0
29
3
1
Order By: Relevance
“…Various studies have shown that AGE-RAGE axis is involved in the development of diabetic complications such as diabetic nephropathy, retinopathy, neuropathy, and cardiomyopathy [24,25,26,27]. Furthermore, in vivo studies have also shown the role of AGE-RAGE in myocardial ischemia reperfusion injury in diabetic rats [8].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that AGE-RAGE axis is involved in the development of diabetic complications such as diabetic nephropathy, retinopathy, neuropathy, and cardiomyopathy [24,25,26,27]. Furthermore, in vivo studies have also shown the role of AGE-RAGE in myocardial ischemia reperfusion injury in diabetic rats [8].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term hyperglycemia causes metabolic disorders due to activation of additional polyol glucose metabolism pathway with increased accumulation of toxic sorbitol in cells of nervous tissue lading to vascular damage (11,12). Furthermore, neuropathy in diabetes is correlated with neurovascular damage not only resulting from metabolic defects, but caused by other risk factors such as hypertension, dyslipidemia, obesity and cigarette smoking (12)(13)(14). Persistent hyperglycemia leads to epithelial cell dysfunction, which results in a decrease of pro-angiogenic signalling and production of nitric oxide (NO) (13).…”
Section: Molecular Basis Of Diabetic Foot Ulcersmentioning
confidence: 98%
“…Persistent hyperglycemia leads to epithelial cell dysfunction, which results in a decrease of pro-angiogenic signalling and production of nitric oxide (NO) (13). NO additionally causes relaxation of smooth muscle, and its absence decreases vasodilatation effectively leading to limb/nerve ischemia (12,14). The neuropathy and poor local blood flow added with the impaired immune function of diabetic patients due to defects in leukocyte functions in hyperglycaemia, results in an inadequate inflammatory response at the site of concern (11, 12).…”
Section: Molecular Basis Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…Several studies focused on diabetics, though not all [177], likewise find that ADMA is a negative prognostic factor for cardiovascular health [154,178,179,180,181,182]. Moreover, a number of case-control studies have reported higher ADMA levels in diabetics afflicted with nephropathy retinopathy, or neuropathy [183,184,185,186,187,188,189,190]. Higher ADMA also was found in diabetics with vertebral fractures, likely reflecting a role for eNOS in bone health [191,192].…”
Section: Citrulline Can Counter the Adverse Impact Of Adma And Argmentioning
confidence: 99%